\[\boxed{\mathbf{575\ (575).\ }Еуроки\ - \ ДЗ\ без\ мороки}\]
\[1)\ y = \sqrt{9 - 8x - x^{2}} + \frac{x + 3}{x^{2} - 2x}\]
\[\left\{ \begin{matrix} 9 - 8x - x^{2} \geq 0 \\ x^{2} - 2x \neq 0\ \ \ \ \ \ \\ \end{matrix} \right.\ \text{\ \ \ \ \ \ \ \ \ \ \ }\]
\[\ \left\{ \begin{matrix} x^{2} + 8x - 9 \leq 0 \\ x(x - 2) \neq 0\ \ \ \ \ \\ \end{matrix} \right.\ \]
\[\left\{ \begin{matrix} (x + 9)(x - 1) \leq 0 \\ x \neq 0\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \\ x \neq 2\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \\ \end{matrix} \right.\ \]
\[Ответ:x \in \lbrack - 9;0) \cup (0;1\rbrack.\]
\[2)\ y = \sqrt{6x - x^{2}} + \frac{3}{\sqrt{x - 3}}\]
\[\left\{ \begin{matrix} 6x - x^{2} \geq 0 \\ x - 3 > 0\ \ \ \ \\ \end{matrix} \right.\ \text{\ \ \ \ \ \ \ \ \ \ }\]
\[\text{\ \ }\left\{ \begin{matrix} x(6 - x) \geq 0 \\ x > 3\ \ \ \ \ \ \ \ \ \ \ \ \ \ \\ \end{matrix} \right.\ \]
\[Ответ:x \in (3;6\rbrack.\]
\[\boxed{\mathbf{575.\ }Еуроки\ - \ ДЗ\ без\ мороки}\]
\[Пусть\ по\ увеличению\ углы\]
\[\ треугольника\ x_{1},\ x_{2},\ x_{3},\ \]
\[тогда\ \ x_{2} = \frac{x_{1} + x_{3}}{2}.\]
\[По\ теореме\ о\ сумме\ углов\]
\[\ треугольника:\text{\ \ }x_{1} + x_{2} + x_{3} =\]
\[= 180{^\circ},\ тогда\ \]
\[2x_{2} + x_{2} = 180{^\circ}\ \]
\[3x_{2} = 180\ \]
\[x_{2} = 60.\]
\[Ответ:средний\ по\ величине\]
\[\ угол\ равен\ 60{^\circ}.\]